1032 The Niemann-Pick Type C Suspicion Index Tool: Examination of its Discriminatory Power by Age and Associations by Leading Symptoms. (October 2012) - Hendriksz, CJ; Pineda, M; Wijburg, FA; Sedel, F; Fahey, M; Walterfang, M; Patterson, MC; Chadha-Boreham, H; Kolb, SA; Wraith, JE
Abstract : Background and Aims: The Suspicion Index (SI) screening tool was developed to identify suspected patients with Niemann-Pick disease type C (NP-C, Neurology, 2012). The SI provides Risk Prediction Score (RPS) based on NP-C symptoms within and across domains (visceral, neurological, and psychiatric). To further examine a) discriminatory power of the SI by age and b) symptom-associations by NP-C suspicion-level and leading symptoms. Methods: The original retrospective data were split into three age groups, where NP-C positive cases were: >16 years (n=30), 4–16 years (n=18), and < 4 years (n=23), and patients' RPS was analysed by logistic regression. Co-occurrence of symptoms within groups of suspicion-level (low, medium, and high) and leading symptoms (presence/absence of ataxia, cognitive decline, psychosis, and splenomegaly) were analysed descriptively. Results: NP-C positive cases vs. controls showed strong discriminatory power of RPS. Area under the Receiver Operating Characteristic curve was 0.964 (>16 years) and 0.981 (4–16 years) but a weaker 0.562 for infants (< 4 years). Patients with RPS < 70 were characterised by a lack of psychiatric symptoms and low levels of neurological involvement, suggestive of a more visceral phenotype. In patients >4 years, prominent leading symptoms' associations were: ataxia with "dystonia, dysarthria/dysphagia and cognitive decline"; psychosis with "dysarthria/dysphagia"; and psychotic symptoms with "cognitive decline and treatment-resistant psychiatric symptoms". Conclusions: The SI tool maintains strong discriminatory power in patients >4 years but is not as useful for infants < 4 years. The SI is informative regarding the association and co-occurrence of symptoms in patients with NP-C.